(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Adult females of Apiomorpha Riibsaamen are remarkably long-lived (up to five years) and those of most species are able to produce thousands of offspring. Males rarely live more than one year ant.! survive only several days after merging from their galls. Males and females of the one cohort mature at about the same time despite extreme size differences between the sexes, thereby allowing brother-sister matings. Age to maturity ranges among species from two and a half months to more than 12 months. The longevity of females results in the overlap of generations of females on the one host plant.